Contextual Process Digitalization Changing Perspectives - Design Thinking - Value-Led Design - Fleischmann, Albert (Springer Nature, 2020)
This open access book presents an overview and step-by-step explanation of process management. It starts with the individual participants' perspectives on their work in a process and its structuring and harmonization, and then moves on to its specification in a model and how it is embedded in the organizational and IT environment of the company. Lastly, the book examines the joint processing of instances in the resulting socio-technical systems. A corresponding illustration, which expands with the overview, enables readers to gain a comprehensive understanding of business process management. The book presents various facets of business process management from the perspective of the participants, and introduces a selection of models that have proved useful in practice. The design of such models supports the transition from a more-or-less unstructured or unsatisfactory way of working to a structured process that corresponds to the ideas of the company and its customers. The book is intended for professionals in industry as well as students in the field of business information systems who are looking for guidelines on how to discover, create and implement real-world processes.